A Development of Inventory Management System for Goat Farm - Mohd Tahar, Hareena Fatini; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2022)
Goat farming in Malaysia is a potentially bright industry and the government has earned widespread attention. Inventory documentation for farms is very important for the plantation industry for the purpose of continuing farm supply chain management. These include databases of food inventories and stocks of veterinary drugs. Inventory data on goat farms for own or small businesses continue to use conventional methods at present. For the management of stock and inventory data on the farm, paper notes, whiteboard notes or books and physical files are also used. However, the methods of storing physical data may cause some difficulties in today's fast-paced and fast-paced environment and cause process inefficiencies, particularly storage and reporting. Therefore, to manage inventory information on goat farms, a web-based inventory system was developed. The system function modules consist of registration modules, human resource module, material modules, account modules also report modules. The functions offered in this framework are capable of solving knowledge management issues and delivering creativity in terms of time savings and the opportunity to access information more effectively. With prototype methods and a structured approach to system design, the scheme was developed. Meanwhile, to write system programs, the PHP programming language is used, and MySQL as the system database. It is hoped that this system would promote the management of food inventory details on the farm by the parties concerned.